2021
DOI: 10.1007/s10787-021-00801-2
|View full text |Cite
|
Sign up to set email alerts
|

Green-lipped (greenshell™) mussel (Perna canaliculus) extract supplementation in treatment of osteoarthritis: a systematic review

Abstract: Objectives Intervention studies using New Zealand green-lipped or greenshell™ mussel (GSM) (Perna canaliculus) extract in osteoarthritis (OA) patients have shown effective pain relief. This systematic review summarises the efficacy of GSM extracts in the treatment of OA. Methods A literature search of the three databases EMBASE, MEDLINE, and Scopus was performed to identify relevant articles published up to March 2020. Inclusion criteria were clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
4
1
Order By: Relevance
“…Moreover, in DMM-induced OA mice, oral administration of WGA-M001 at doses up to 100 mg/kg effectively inhibited cartilage destruction compared to that associated with a high dose (500 mg/kg) of T. erecta or O. basilicum. Recent research has shown that Boswellia and P. canaliculus are well-known OA-alleviating substances [41,55,56]. However, our study demonstrated that WGA-M001 had a stronger protective effect against OA development compared to the effect of the positive controls.…”
Section: Discussioncontrasting
confidence: 67%
“…Moreover, in DMM-induced OA mice, oral administration of WGA-M001 at doses up to 100 mg/kg effectively inhibited cartilage destruction compared to that associated with a high dose (500 mg/kg) of T. erecta or O. basilicum. Recent research has shown that Boswellia and P. canaliculus are well-known OA-alleviating substances [41,55,56]. However, our study demonstrated that WGA-M001 had a stronger protective effect against OA development compared to the effect of the positive controls.…”
Section: Discussioncontrasting
confidence: 67%
“…In the second trial, GSM powder was compared to glucosamine sulfate in a 12 week intervention where both supplements showed equal effectiveness on the aforementioned outcome measures ( 18 ). Our recent systematic review on the existing clinical trials concluded that both GSM lipid extract or whole meat powder products provide a clinically meaningful improvement in VAS pain for OA symptoms ( 44 ). In terms of knee related symptoms, the GSM group showed a greater improvement in KOOS symptoms domain overtime, although the change was not significant and did not reach the suggested minimal clinical improvement (at least eight points improvement) ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recently, a New Zealand research group reported that the addition of oil from GSM to the diet of diet-induced metabolic OA rats resulted in both decreased plasma levels of the C telopeptide of type II collagen (CTX-II), which is known as a biomarker of cartilage degradation, and a cartilage protective effect in histology [ 41 ]. The same research group also reported that the use of GSM whole extract or lipid extract reduced the VAS pain scores of knee/hip OA patients in a systematic review [ 42 ]. They also reported that both VAS pain scores and plasma CTX-II levels decreased in postmenopausal women with obesity who received 3 g/day of whole GSM powder compared to those who received placebo [ 43 ].…”
Section: Functional Ingredients Of Health Functional Foods For Oa In ...mentioning
confidence: 99%